Pengisian Air Dan Nutrisi Otomatis Pada Reservoir Hidroponik Kratky Untuk Budidaya Pakcoy (Brassica Rapa Subsp Chinensis): PENGISIAN AIR DAN NUTRISI OTOMATIS PADA RESERVOIR HIDROPONIK KRATKY UNTUK BUDIDAYA PAKCOY (Brassica rapa subsp chinensis) - Anri Kurniawan; Hanif Nur Fatih; Hanis Adila Lestari (Jurnal Agritechno, 2025)
The automated water and nutrient filling system in the Kratky hydroponic method for pak choi (Brassica rapa subsp. chinensis) is designed to control the reservoir’s water level and nutrient concentration. An ultrasonic sensor measures the water surface height, while a TDS sensor monitors nutrient concentration. Both sensors are controlled by an Arduino Uno microcontroller, which manages the operation of the water and nutrient pumps. This study aimed to design and test the automated filling system. The research involved tool development, system testing, and data analysis through calibration using percentage error and Root Mean Square Error (RMSE) to evaluate the pump’s performance. The results showed that the system functioned optimally: the water pump was activated when the water level ranged between 30 and 40 cm, and the nutrient pump operated when the ppm value fell below 600. The ultrasonic sensor had an error of 0.76%, and the TDS sensor 0.60%, both under 1%, indicating high accuracy. At 30 days after transplanting, the pak choi plants had an average height of 15.05 cm and a leaf width of 14.98 cm. The water pump performance under the automated filling system had an RMSE value of 7.5498, indicating good reliability.